ANTIBIOTIC USE IN SLOVENIAN HOSPITALS - Pokrajac, Tatjana; Čižman, Milan; Beovič, Bojana (International Journal of Research -GRANTHAALAYAH, 2019)
Abstract: Motivation/Background: Antibiotics are commonly overused and misused what increase the emergence of resistant organisms, side- effects and costs. To assess the appropriate use of antibiotics many methods are available. The aim of the present study is to find correlation between antibiotic use and case mix index (CMI) in Slovenian hospitals. Method: In retrospective study (in the years between 2004 and 2013) we correlated the total consumption of antibiotics for systemic use and CMI. Weighted linear regression test analysis was performed to determine correlation between defined daily dose (DDD) / 100 admissions and DDD / 100 bed-days and CMI. Results: The total antibiotic consumption in all included hospitals was in mean 317.69 DDD / 100 admissions and 58.88 DDD / 100 bed days, respectively. CMI range were from 1.25 to 3.55. A significant correlation between consumption expressed in DDD / 100 admissions and CMI (p = 0.028) and DDD / 100 bed days and CMI (p =0.008) was found. Conclusions: Thus, detailed analysis of correlations between DDD of antibiotics and CMI may constitutes a proper use of antibiotics.